Acute Hormonal Responses Before and After 2 Weeks of HIT in Well Trained Junior Triathletes - Zinner, C.; Wahl, P.; Achtzehn, S.; Reed, J. L.; Mester, J. (International Journal of Sports Medicine, 2014)
The aim was to compare the acute hormonal response to a single HIT session at the beginning and end of a HIT shock microcycle. 13 male junior triathletes (15.8±1.8 yrs.) performed 16 HIT sessions within a 2 week period. Venous blood samples were collected before and after the first and last HIT session. Significant increases in cortisol (first session +89.7%; last session +70.3%) and hGH (first session +435.1%; last session +314.6%) concentrations were observed after both training sessions (P<0.05). The acute responses of cortisol, hGH, T3, and fT3 were not different between the first and last HIT sessions (P=1.00). Although no acute changes in testosterone were detected after the training sessions, testosterone concentrations were significantly higher at all time points (62.6–80.1%) during the last compared to first training session (P≤0.001). Findings from the present study reveal that 16 sessions of HIT led to significant increases in baseline concentrations of serum testosterone. This might indicate a heightened anabolic state even in junior triathletes. Based on the hormonal data, we conclude that at the end of this 2 week microcycle no familiarization effect was evident and that the training stimulus produced by HIT was still great enough to “stress” the athletes and induce positive training adaptations.
Keywords: endocrine system; testosterone; triathlon; triiodothyronine; shock microcycle; young athletes; interval training